Determinantes da arrecadação do Imposto sobre Serviço de Qualquer Natureza (ISSQN) nos municípios do Estado do Ceará no período de 2012 a 2017 - Castelo, Luis Adauto Marinho (2020)
The present study aims to analyze the interference of determining factors in the collection of the Tax of Any Nature Service (ISSQN) in the municipalities of the State of Ceará from 2012 to 2017. The determining factors studied were the population, municipal Gross Domestic Product and intergovernmental transfers. Proposal the hypothesis that these factors would be responsible for the fundraising expansion of the ISSQN. The research was based on the application of the paneled data method and a transformation and its data were collected from secondary sources, mainly IBGE and the Brazil's Finance System (FINBRA) with the values being deflated by the National Consumer Prices (INPC). After the study of the collected data, it was concluded that the elasticity of the population growing by 1% the collection of ISSQN suffers a decrease in 0.55% contrary to all previous possibilities; the elasticity of GDP was effective in the sense that 1% increase in GDP puts an increase of 0.97% in the collection of ISSQN; already in the elasticity of intergovernmental transfers 1% increase in transfers positively interferes with 0.65% in ISSQN revenue.